A comprehensive review of Wolbachia-mediated mechanisms to control dengue virus transmission in Aedes aegypti through innate immune pathways - Mushtaq, Iqra; Sarwar, Muhammad Sajjad; Munzoor, Iqra (Frontiers in Immunology, 2024)
The Dengue virus (DENV), primarily spread by Aedes aegypti and also by Aedes albopictus in some regions, poses significant global health risks. Alternative techniques are urgently needed because the current control mechanisms are insufficient to reduce the transmission of DENV. Introducing Wolbachia pipientis into Ae. aegypti inhibits DENV transmission, however, the underlying mechanisms are still poorly understood. Innate immune effector upregulation, the regulation of autophagy, and intracellular competition between Wolbachia and DENV for lipids are among the theories for the mechanism of inhibition. Furthermore, mainly three immune pathways Toll, IMD, and JAK/STAT are involved in the host for the suppression of the virus. These pathways are activated by Wolbachia and DENV in the host and are responsible for the upregulation and downregulation of many genes in mosquitoes, which ultimately reduces the titer of the DENV in the host. The functioning of these immune pathways depends upon the Wolbachia, host, and virus interaction. Here, we summarize the current understanding of DENV recognition by the Ae. aegypti’s immune system, aiming to create a comprehensive picture of our knowledge. Additionally, we investigated how Wolbachia regulates the activation of multiple genes associated with immune priming for the reduction of DENV.